Testing the effect of social norms theory-based interventions: Are they harmful for university students who drink less than the peer norm? - Kravčenko, Karina; Šeibokaitė, Laura (Psichologija, 2021)
Background. Social norms theory-based interventions have been widely used to reduce alcohol consumption among college and university students. Lately, it has been argued that such interventions may actually increase alcohol use among light drinkers. However, little studies have been focused on testing this possible negative effect. Objectives. The aim of this study was to examine possible negative impact of descriptive normative feedback (DNF) on drinking intentions among students whose baseline drinking scores were below the average of a reference group. We also studied the preventive effect of injunctive normative feedback (INF). Methods. Actual descriptive and injunctive norms were collected from 234 university students. From those who reported drinking below the norm, 26 were randomly assigned to a control or intervention condition that received normative feedback via PowerPoint presentations over two meetings. Results. DNF increased students’ intentions of spirits drinking frequency and quantity. Meanwhile intentions to drink beer, cider, wine and cocktails remained the same. Increased intentions to drink spirits were not reduced by INF. Conclusions. Findings suggest that DNF-based interventions might negatively affect the use of spirits among those students who consume less than their peer norm by increasing their intentions to drink spirits more often and in larger quantities. Ways other than the INF to prevent this negative effect need to be further explored.